Modelling impacts of lateral N flows and seasonal warming on an arctic footslope ecosystem N budget and N2O emissions based on species-level responses - Rasmussen, Laura H.; Zhang, Wenxin; Ambus, Per; Jansson, Per Erik; Kitzler, Barbara; Elberling, Bo (Biogeochemistry, 2022)
Future Arctic tundra primary productivity and vegetation community composition will partly be determined by nitrogen (N) availability in a warmer climate. N mineralization rates are predicted to increase in both winter and summer, but because N demand and –mobility varies across seasons, the fate of mineralized N remains uncertain. N mineralized in winter is released in a “pulse” upon snowmelt and soil thaw, with the potential for lateral redistribution in the landscape. In summer, the release is into an active rhizosphere with high local biological N demand. In this study, we investigated the ecosystem sensitivity to increased lateral N input and near-surface warming, respectively and in combination, with a numerical ecosystem model (CoupModel) parameterized to simulate ecosystem biogeochemistry for a tundra heath ecosystem in West Greenland. Both measurements and model results indicated that plants were poor utilizers of increased early-season lateral N input, indicating that higher winter N mineralization rates may have limited impact on plant growth and carbon (C) sequestration for a hillslope ecosystem. The model further suggested that, although deciduous shrubs were the plant type with overall most lateral N gain, evergreen shrubs appear to have a comparative advantage utilizing early-season N. In contrast, near-surface summer warming increased plant biomass and N uptake, moving N from soil to plant N pools, and offered an advantage to deciduous plants. Neither simulated high lateral N fluxes nor near-surface soil warming suggests that mesic tundra heaths will be important sources of N2O under warmer conditions. Our work highlights how winter and summer warming may play different roles in tundra ecosystem N and C budgets depending on plant community composition.